2021
DOI: 10.1029/2020ef001655
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Biomass Turnover Times in Tropical Forests and Their Environmental Drivers From 2001 to 2012

Abstract: Tropical forests play a key role in the global carbon (C) cycle and the climate system (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 94 publications
(213 reference statements)
0
3
0
Order By: Relevance
“…Over the past 20 years, the global NPP generally displayed an increasing trend with significant improvements in tropical rainforests in Africa [34], subtropical regions [35], and the alpine Tibetan Plateau in China [36]. In contrast, the vegetation NPP monitored in Southeast Asia [37], western Amazonian tropical rainforests [37], temperate desert-steppe in Inner Mongolia of China [38], and semi-dry grasslands in Australia showed a decreasing trend [39]. Gang et al found that the main changes in grassland NPP were positively correlated with precipitation (PRE) after comparing the analyses of grassland NPP in China, North America, Europe, and Australia from 1981 to 2010 [10].…”
Section: Introductionmentioning
confidence: 99%
“…Over the past 20 years, the global NPP generally displayed an increasing trend with significant improvements in tropical rainforests in Africa [34], subtropical regions [35], and the alpine Tibetan Plateau in China [36]. In contrast, the vegetation NPP monitored in Southeast Asia [37], western Amazonian tropical rainforests [37], temperate desert-steppe in Inner Mongolia of China [38], and semi-dry grasslands in Australia showed a decreasing trend [39]. Gang et al found that the main changes in grassland NPP were positively correlated with precipitation (PRE) after comparing the analyses of grassland NPP in China, North America, Europe, and Australia from 1981 to 2010 [10].…”
Section: Introductionmentioning
confidence: 99%
“…Wang et al. (2020) analysed temporal trends in τ in tropical forests from 2001 to 2012 using remote‐sensing‐based biomass and NPP datasets. They observed that τ was statistically associated with mean annual precipitation (MAP), radiation, and vapour pressure deficit.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Carvalhais et al (2014) calculated the global spatial distribution of τ using multiple sources of carbon stock and flux data, and found a strong association of τ with precipitation and temperature. Wang et al (2020) analysed temporal trends in τ in tropical forests from 2001 to 2012 using remote-sensing-based biomass and NPP datasets. They observed that τ was statistically associated with mean annual precipitation (MAP), radiation, and vapour pressure deficit.…”
mentioning
confidence: 99%